Temporal trends in complex PCI interventions. (3rd October 2022) - Kheifets, M; Vons, S A; Bental, T; Vaknin-Assa, H; Perl, L; Kornowski, R; Levi, A
Abstract: Background: Accumulated experience combined with technological advancements in the field of complex percutaneous coronary intervention (C-PCI), have led to a gradual increase in both quantity and complexity of PCI procedures over the last 20 years. Despite the amount and frequency of these complex interventions, data regarding outcomes is lacking. Methods: The study was based on a prospective registry of 20, 301 consecutive procedures with a follow up of at least 1 year. C-PCIs were defined as at least one of the following: Chronic total occlusion (CTO), left main (LM), bifurcation or saphenous vein graft (SVG) PCI. We compared trends during four different time periods (2008–2010, 2011–2013, 2014–2016, 2017–2019). Endpoints included mortality and major adverse cardiac events [MACE: death, repeat myocardial infarction (re-MI), and target vessel revascularization (TVR)] at 1 year. Results: The rate of C-PCI procedures has risen significantly since 2017 (p<0.01), driven mainly by bifurcation and LM interventions (p<0.01). At 1-year, rates of death (p<0.001), re-MI (p<0.001), TVR (p=0.001) and MACE (p<0.001), were all significantly higher in the C-PCI group, as compared to the non-complex group. Rates of TVR (p=0.01) and MACE (p<0.001) at 1-year, were significantly higher in the C-PCIs which were performed between 2008–2010 and 2011–2013, as compared to C-PCIs performed between 2014–2016 and 2017–2019. Death rates did not significantly differ between C-PCI periods. Conclusions: Although frequency of C-PCIs is on the rise, overall outcomes become increasingly better, as compared to earlier periods. Unfortunately, this has not translated into a decrease in mortality. Funding Acknowledgement: Type of funding sources: None.